Lived experience after bariatric surgery among patients with morbid obesity in east coast Peninsular Malaysia: a qualitative study - Gullaam Rasul, Siti Faezah; Draman, Nani; Muhamad, Rosediana; Mat Yudin, Zainab; Abdul Rahman, Razlina; Draman, Samsul; Md Hashim, Mohd Nizam (MDPI, 2022)
Living with morbid obesity is challenging since it affects various dimensions of life. Sustainable weight loss via bariatric surgery helps people suffering from morbid obesity to lead a healthy and meaningful life. This study highlights the challenges before bariatric surgery and the impact on one’s life. A phenomenological approach was employed using in-depth interviews with 21 participants (15 females and 6 males) who had undergone surgery at least 6 months prior to the study with the mean age of 42.6 years. Due to excess body weight, the physical limitation had a serious negative impact on their social life, making them targets of bias and stigmatisation. Surgery was the best option for them to attain sustainable weight loss and to lead a new life. However, a few participants struggled with the side effects of surgery. Five themes were discovered, namely, (1) social restraint; (2) experiencing bias and stigmatisation; (3) bringing new life; (4) boosting self-esteem; and (5) facing the negative side of surgery. This study serves as a platform to explore the difficulties faced by people with morbid obesity and the changes that the participants experienced after the surgery for future intervention to curb the rising number of people with morbid obesity.